2013
DOI: 10.2478/hukin-2013-0083
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Anthropometric, Kinematic and Energetic Variables and Gender on Swimming Performance in Youth Athletes

Abstract: The aim of this study was to assess the: (i) gender; (ii) performance and; (iii) gender versus performance interactions in young swimmers’ anthropometric, kinematic and energetic variables. One hundred and thirty six young swimmers (62 boys: 12.76 ± 0.72 years old at Tanner stages 1–2 by self-evaluation; and 64 girls: 11.89 ± 0.93 years old at Tanner stages 1–2 by self-evaluation) were evaluated. Performance, anthropometrics, kinematics and energetic variables were selected. There was a non-significant gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 22 publications
(44 reference statements)
3
32
2
1
Order By: Relevance
“…This means that the swimmers are submitted to high volumes, based on aerobic sets, improvement of the swim efficiency, and dry-land S&C. At the first moment (M1), the clusters were characterized by different determinants (cluster 1: a high squat jump, throwing velocity, and swimming velocity; cluster 2: a high intracyclic swimming velocity and a low stroke index and swimming velocity; cluster 3: a high propelling efficiency and a low arm span and throwing velocity). Some studies have reported that the fastest swimmers, besides having better nature aspects (high body dimensions), also have better kinematics (i.e., swimming velocity) compared to their slower counterparts Morais et al, 2013). However, little is known about the role of S&C programs in this regard.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This means that the swimmers are submitted to high volumes, based on aerobic sets, improvement of the swim efficiency, and dry-land S&C. At the first moment (M1), the clusters were characterized by different determinants (cluster 1: a high squat jump, throwing velocity, and swimming velocity; cluster 2: a high intracyclic swimming velocity and a low stroke index and swimming velocity; cluster 3: a high propelling efficiency and a low arm span and throwing velocity). Some studies have reported that the fastest swimmers, besides having better nature aspects (high body dimensions), also have better kinematics (i.e., swimming velocity) compared to their slower counterparts Morais et al, 2013). However, little is known about the role of S&C programs in this regard.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the stroke kinematics (stroke frequency and swimming velocity) and height (H) were the best cluster discriminators. The reports in the literature consistently indicate that anthropometrics and kinematics are strongly related to the performance of young swimmers Mezzaroba and Machado, 2014;Vitor and Böhme, 2010), with the fastest swimmers having better kinematics (Morais et al, 2013;Tsalis et al, 2012). The "talented" swimmers (cluster 1) presented a well-rounded set of determinants, which included being the tallest (height, anthropometrics), fastest (swimming velocity, kinematics) and strongest (throwing velocity, upper limb S&C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is claimed that heredity determines the body length (height, limb and foot length) by as much as 70 percent, while fat and muscle mass -by 20-40 percent (Bouchard, Malina, & Perusse, 1997;Issurin, 2017). Earlier studies have shown that longitudinal anthropometric dimensions are important for predicting swimmers' athletic performance and can be considered as selection criteria at a young age (Issurin, 2017;Kjendlie & Stallman, 2011;Morais at al., 2013;Sammoud et al, 2018).…”
Section: Peculiarities Of Changes Of Young Swimmers' Anthropometric Pmentioning
confidence: 99%
“…Os parâmetros da marcha, tal como os de outros movimentos, vão alterando ao longo do crescimento das crianças (Beck et al, 1981;Morais et al, 2013). Este autor determinou num grupo de crianças entre 11 meses e 14 anos de idade as velocidades mais lentas e mais rápidas observadas na marcha.…”
Section: Ciclo Da Marchaunclassified